Pengaruh Makro Ekonomi Terhadap Profitabiltas Bank Umum Syariah di Indonesia Tahun 2014-2018 - Wahyudin Priyono; Imanda Firmantyas Putri Pertiwi (Universitas Islam Negeri Raden Mas Said Surakarta, 2019)
This study aims to analyze and identify the effects of inflation and rupiah exchange rates on profitability in Islamic banks in Indonesia with mudharabah deposit as the mediator. Using secondary data that are published by the central bank of Indonesia and financial services authority, the method used in this research is Ordinary Least Square. The result indicates the inflation variable, exchange rate, and mudharabah deposits simultaneously give a significant influence toward profitability (ROA) of the Sharia Commercial Bank in Indonesia. While partially, inflation and exchange rate have no significant effect on profitability (ROA). While mudharabah deposits have a significant positive effect on profitability (ROA). Inflation has a significant negative effect on mudharabah deposits and the exchange rate has a significant positive effect on mudharabah deposits. The path analysis result shows that the mudharabah deposit variable is unable to mediate the effect of inflation and te exchange rate to profitability (ROA)